2019
DOI: 10.15789/1563-0625-2019-3-467-478
|View full text |Cite
|
Sign up to set email alerts
|

CD39<sup>+</sup> EXPRESSION BY REGULATORY T CELLS IN PULMONARY SARCOIDOSIS AND LOFGREN’S SYNDROME

Abstract: Sarcoidosis is a disorder of unknown etiology characterized by development of necrosis-free epithelioid cell granulomas in various tissues. There are two main phenotypes of pulmonary sarcoidosis (PS): Lofgren’s syndrome (LS) is an acute form with favorable outcome, while non-Lofgren’s syndrome (nLS) is a chronic type of disease that can lead to pulmonary fibrosis in 20% of cases.Our study was aimed at investigating changes in the main cell-surface differentiation antigens on peripheral blood regulatory T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
1
1
3
Order By: Relevance
“…Ki-67, a marker of recent cell division, was upregulated in sarcoidosis PBMCs, in CD4 + and CD8 + T cells, and most substantially in Tregs ( Figure 1C ), suggesting ongoing clonal activation of T cells with compensatory division of Tregs. In contrast to previously reported data ( 4 , 14 , 15 ), we found that the CD45RO effector/memory subset in sarcoidosis Tregs was decreased, with no differences in expression of CTLA-4 and CD39 ( Supplementary Figures S2B–D ). CXCR5 was upregulated in sarcoidosis Tregs and CD8 + cells, but CD4 + CXCR5 + T follicular helper cell numbers were not affected ( Supplementary Figure S2E ).…”
Section: Resultscontrasting
confidence: 99%
“…Ki-67, a marker of recent cell division, was upregulated in sarcoidosis PBMCs, in CD4 + and CD8 + T cells, and most substantially in Tregs ( Figure 1C ), suggesting ongoing clonal activation of T cells with compensatory division of Tregs. In contrast to previously reported data ( 4 , 14 , 15 ), we found that the CD45RO effector/memory subset in sarcoidosis Tregs was decreased, with no differences in expression of CTLA-4 and CD39 ( Supplementary Figures S2B–D ). CXCR5 was upregulated in sarcoidosis Tregs and CD8 + cells, but CD4 + CXCR5 + T follicular helper cell numbers were not affected ( Supplementary Figure S2E ).…”
Section: Resultscontrasting
confidence: 99%
“…Ранее нами был проведен анализ содержания некоторых популяций и субпопуляций Т-и В-лимфоцитов при саркоидозе. Описано содержание на разных стадиях дифференцировки цитотоксических Т-лимфоцитов, особенностей состава регуляторных Т-лимфоцитов, а также изменение субпопуляционного состава В-лимфоцитов в периферической крови больных саркоидозом при разной степени активности заболевания [1,4,5,6,7]. Известно, что направленную миграцию клеток в ткани обеспечивают лиганды для определенных рецепторов, экспрессирующихся на клеточной мембране.…”
Section: Discussionunclassified
“…[84]. When comparing the level of expression of CD39 on regulatory T-cells of peripheral blood, it turned out that the relative content of CD39 + cells is increased both in patients with acute onset and in primary chronic sarcoidosis [85]. It is likely that the formation of anti-inflammatory adenosine, which is involved in the suppression of hypersensitive immune responses, is one of the key and most common mechanisms of immunosuppression in both acute and chronic sarcoidosis.…”
Section: Typical Biopsymentioning
confidence: 99%